Label-free SERS detection of Raman-Inactive protein biomarkers by Raman reporter indicator: Toward ultrasensitivity and universality - Arabi, Maryam; Ostovan, Abbas; Zhang, Zhiyang; Wang, Yunqing; Mei, Rongchao; Fu, Longwen; Wang, Xiaoyan; Ma, Jiping; Chen, Lingxin (Biosensors & bioelectronics, 2021)
It is still challenging to sensitively detect protein biomarkers via surface-enhanced Raman scattering (SERS) technique owing to their low Raman activity. SERS tag-based immunoassay is usually applied; however, it is laborious and needs specific antibodies. Herein, an ultrasensitive and universal “Raman indicator” sensing strategy is proposed for protein biomarkers, with the aid of a glass capillary-based molecularly imprinted SERS sensor. The sensor consists of an inner SERS substrate layer for signal enhancement and an outer mussel-inspired polydopamine imprinted layer as a recognition element. Imprinted cavities have two missions: first, selectively capturing the target protein, and second, the only passageway of Raman indicator to access SERS substrate. Specific protein recognition means filling imprinted cavities and blocking Raman indicator flow. Thus, the quantity of captured protein can be reflected by the signal decrease of ultra-Raman active indicator molecule. The capillary sensor exhibited specific and reproducible detection at the level down to 4.1 × 10−3 μg L−1, for trypsin enzyme in as-received biological samples without sample preparation. The generality of the mechanism is confirmed by using three different protein models. This platform provides a facile, fast and general route for sensitive SERS detection of Raman inactive biomacromolecules, which offers great promising utility for in situ and fast point-of-care practical bioassay. [Display omitted] •Label-free “Raman indicator” sensing strategy was proposed for biomarker detection.•Commercial glass capillary substrate was used to improve synthesis reproducibility.•MIP-SERS sensor enabled fast biomarker sensing in 50 μL of crude biological samples.•Ultra-low detection limit of 4.1 × 10−3 μg L−1 was obtained for trypsin enzyme.